Chapter Per la critica della crescita illimitata e della crescita verde - Bellanca, Nicolò (Studi e saggi, 2020)
We focus on two great narratives: unlimited growth and green growth. The problem of the compatibility between the increase of human economic activities and the ecosystem seems to be solved by each of the two narratives. After recalling the thermodynamic unfoundedness of the first paradigm, we ask ourselves why it remains central in orienting political choices. Our answer explores the nature of "public religion" that economics has been taking on: by shaping our mental models and our actions, today's dominant economic theory is capable of converting us, contributing to the affirmation of even indefensible beliefs. With regard to the green growth paradigm, it is based on the idea of an absolute decoupling between the trend of growth and the negative impact on the environment, as well as on the related idea that forms of full circularity of economic processes are practicable. Against this conception theoretical arguments and empirical evidence have been advanced, none of which is in itself negatively conclusive, but whose complex makes it highly implausible.